2009
DOI: 10.1074/jbc.m109.005652
|View full text |Cite
|
Sign up to set email alerts
|

Role of the General Base Glu-268 in Nitroglycerin Bioactivation and Superoxide Formation by Aldehyde Dehydrogenase-2

Abstract: Mitochondrial aldehyde dehydrogenase-2 (ALDH2) plays an essential role in nitroglycerin (GTN) bioactivation, resulting in formation of NO or a related activator of soluble guanylate cyclase. ALDH2 denitrates GTN to 1,2-glyceryl dinitrate and nitrite but also catalyzes reduction of GTN to NO. To elucidate the relationship between ALDH2-catalyzed GTN bioconversion and established ALDH2 activities (dehydrogenase, esterase), we compared the function of the wild type (WT) enzyme with mutants lacking either the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 37 publications
4
34
0
Order By: Relevance
“…In 2002, Stamler and coworkers (Chen et al, 2002) showed that ALDH2 denitrates GTN to 1,2-glyceryl dinitrate (1,2-GDN) and nitrite and proposed that reduction of nitrite by components of the mitochondrial electron transfer chain could provide the link between ALDH2-catalyzed GTN metabolism and vasorelaxation. However, we found that 1) GTN activates sGC in the presence of purified ALDH2 , 2) ALDH2 catalyzes the reduction of GTN to NO, accounting for 5 to 10% of total GTN turnover (Beretta et al, 2008a;Wenzl et al, 2009), and 3) mitochondrial biotransformation of nitroglycerin is not affected by respiratory substrates or inhibitors (Kollau et al, 2009), suggesting that ALDH2 catalysis is sufficient for GTN bioactivation in blood vessels.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In 2002, Stamler and coworkers (Chen et al, 2002) showed that ALDH2 denitrates GTN to 1,2-glyceryl dinitrate (1,2-GDN) and nitrite and proposed that reduction of nitrite by components of the mitochondrial electron transfer chain could provide the link between ALDH2-catalyzed GTN metabolism and vasorelaxation. However, we found that 1) GTN activates sGC in the presence of purified ALDH2 , 2) ALDH2 catalyzes the reduction of GTN to NO, accounting for 5 to 10% of total GTN turnover (Beretta et al, 2008a;Wenzl et al, 2009), and 3) mitochondrial biotransformation of nitroglycerin is not affected by respiratory substrates or inhibitors (Kollau et al, 2009), suggesting that ALDH2 catalysis is sufficient for GTN bioactivation in blood vessels.…”
Section: Introductionmentioning
confidence: 94%
“…The mechanism underlying ALDH2-catalyzed GTN reduction is not known, but the reaction seems to occur within the active site pocket with Cys302 serving as the common essential nucleophile (Larson et al, 2007;Wenzl et al, 2009). It was proposed by Stamler and coworkers (Chen et al, 2002) that GTN denitration resembles ester hydrolysis by ALDH2 (Mann and Weiner, 1999) (i.e., nucleophilic attack of a nitro group of GTN by Cys302, resulting in formation of a thionitrate intermediate and release of the corresponding alcohol, preferentially 1,2-GDN).…”
Section: Introductionmentioning
confidence: 99%
“…58 Recent data obtained with purified ALDH-2 provide evidence that ALDH-2 could be a source of GTN-triggered ROS formation. 59 The pathways leading to GTN tolerance in this hypothesis are summarized in Figure 6.…”
Section: Does Oxidative Stress Account For Nitratementioning
confidence: 99%
“…We compared NO-Cbi to direct NO donors, rather than to indirect NO donors such as nitroglycerin or other organic nitrates, because the latter require cellular biotransformation and can increase production of reactive oxygen species [33,34]. The increased potency of NO-Cbi compared to DetaNONOate was particularly surprising, because Deta-NONOate releases two nitric oxide molecules per mole of compound.…”
Section: Discussionmentioning
confidence: 99%